RESPONSE OF WHEAT CULTIVARS (TRITICUM AESTIVUM L.) TO ADDING NITROGEN FERTILIZERS METHODS - Ammar Asaad Abdul Majid Al-Mousa; Waleed Abdulreda Jabail; Khawla Rashige Hassan (European Journal of Agricultural and Rural Education, 2022)
The field study was carried out in Basra Governorate - Al-Haritha District - in the field of Agricultural Research Station - College of Agriculture - University of Basra during the agricultural season 2020-2021 in soil with a clay mixture. To study the response of wheat cultivars to the methods of nitrogen fertilizer addition, the experiment was applied by the split-plot method in a randomized complete block design RCBD with three replications; the experiment included two factors. The first factor is the methods of adding nitrogen fertilizer (banding, middle row, broadcast bands). The second factor includes four types of wheat (Rasheed, Baraka, Abu Ghraib-3, Ibaa-99). The results of the study showed a significant difference between the varieties in most of the studied traits, where the Rasheed variety was superior in the number of spikes (554.78) m2 , The efficiency of the spike (95.46), the number of grains in the spike (53.48) the grain of the spike -1 , the grain yield (5.21) t ha-1 , the biological yield (17.05) t ha-1 , and the harvest coefficient was (30.50) %. In contrast, the cultivar Ibaa- 99 gave the highest average weight of 1000 grains (60.43) g. The results showed that the method of adding urea in a mid-row band was significantly superior in the number of spikes (558.91) spike m2 , spike efficiency (95.86) %, the number of grains per spike (55.97), grain spike-1 , grain yield (5.29) t ha-1 and bio yield (16.99). t ha-1 and the harvest index (31.11) %, while the method of adding urea in broadcast bands gave the highest weight of 1000 grains (54.99) g. The interaction was significant between the varieties and methods of addition in the traits studied, between Rasheed cultivar and the method of adding urea in the mid-row band of the highest average grain yield (6.87) t ha